Increased perceptual and motor performance of the arms of elite water polo players - Gardasevic, J.; Akpinar, S.; Popovic, S.; Bjelica, D. (Applied Bionics and Biomechanics, 2019)
Background. It has been stated that long-term participation in sport training can influence the motor asymmetry of the arms with a decreased interlimb difference. However, whether this pattern is observable in different sports and with different variables, like perceptual performance, still needs to be tested. Therefore, we investigated if long-term sports participation might modify the motor and perceptual performance asymmetries of arms in water polo players. It was hypothesized that water polo players would perform with less interlimb asymmetry in comparison to nonathletes. Methods. Right-handed water polo players and nonathletes were tested on motor performance for both arms during a reaching task. Thirteen water polo players and thirteen nonathletes performed reaching movements under two experimental conditions: (a) right arm and (b) left arm. Velocity, accuracy, hand path deviation from linearity, and reaction time were calculated for each trial and for both arms. The potential interlimb differences in movement performance could be assessed by testing. Results. Consistent with the hypothesis, our findings showed that water polo players displayed substantially less asymmetry in the performance of accuracy and reaction time. Conclusions. These findings suggest that performance asymmetries of arms can be altered via intense long-term practice.